2018
DOI: 10.1021/acs.joc.7b03186
|View full text |Cite
|
Sign up to set email alerts
|

C2′-F Stereoconfiguration As a Puckering Switch for Base Stacking at the Dinucleotide Level

Abstract: Fluorine configuration at C2' of the bis(2'-fluorothymidine) dinucleotide is demonstrated to drive intramolecular base stacking. 2'-β F-Configuration drastically reduces stacking compared to the 2'-α series. Hence, base stacking emerges as being tunable by the C2'-F stereoconfiguration through dramatic puckering variations scrutinized by NMR and natural bond orbital analysis. Accordingly, 2'-β F-isomer photoreactivity is significantly reduced compared to that of the 2'-α F-isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Furthermore, the observed change is in opposition to our hypothesis that a longer-lived excited-state lifetime correlates with a higher CPD yield, therefore lending further credence to the suggested stacking effect by Moriou and co-workers. 30,31 Nonetheless and rather interestingly, we have observed a link between sugar modification and excited-state lifetime. There are a variety of ground-state conformers in thymidine, the relative populations of which are known to change as a function of structural modification, 34,35 and the current result suggests that ground-state conformational diversity may be projected onto the excited state in a way that markedly affects the excited-state dynamics.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the observed change is in opposition to our hypothesis that a longer-lived excited-state lifetime correlates with a higher CPD yield, therefore lending further credence to the suggested stacking effect by Moriou and co-workers. 30,31 Nonetheless and rather interestingly, we have observed a link between sugar modification and excited-state lifetime. There are a variety of ground-state conformers in thymidine, the relative populations of which are known to change as a function of structural modification, 34,35 and the current result suggests that ground-state conformational diversity may be projected onto the excited state in a way that markedly affects the excited-state dynamics.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…27−29 In addition, studies have shown that fluorination at the C2′ position of the sugar ring changes CPD yield: fluorination at the exo position increases the yield, while fluorination at the endo position decreases the yield. 30,31 Speculation about this mechanism has been limited to the sugar conformation affecting the stacking of the bases within the sequence, thus positioning adjacent bases to be closer or further at the moment of excitation. We are interested in whether the excited-state lifetime of the nucleoside alone is modified by the conformation of the sugar when in isolation and this effect instead can play the determining role in defining the CPD yield.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…Another popular anti ‐G substitute is based on the C2′ epimer of F rG, 2′‐deoxy‐2′‐fluoroarabinoguanosine ( F araG). Steered by strong gauche and possibly also steric effects due to the β‐2′‐fluorine, this rather rigid nucleoside tends to adopt a more DNA‐like south‐east/east or C1′‐ exo /O4′‐ endo conformation . Nevertheless, expected unfavorable interactions between the β‐positioned fluorine above the furanose sugar and a syn ‐guanine moiety, together with a potential unconventional intranucleotide hydrogen bond between fluorine and H8 of an anti ‐guanine base, may be advocated as major determinants for its preferred anti conformation …”
Section: Sugar Conformations and Syn‐anti Equilibria Of Guanosine Anamentioning
confidence: 99%
“…13,14 The most recurrent, but rather imprecise conformational factor associated with (6–4) PP formation is the requirement of a certain degree of flexibility of the sugar phosphate DNA backbone. Experimental 15 and theoretical 16 studies have also led to identify the nucleotide sugar conformation as a major determinant in the production of (6–4) adduct at the single-strand di- and oligonucleotide level. However, further experimental studies are still required to provide an in-depth understanding of the role played by the sugar conformation in (6–4) PP production.…”
Section: Introductionmentioning
confidence: 99%